The determinants of household saving behaviour in Malta - William Gatt (Central Bank of Malta, 2014)
This study analyses the determinants of the aggregate household saving rate in Malta; an important macroeconomic variable which in standard short-term analysis is considered as a 'residual'. The aggregate household saving rate, fluctuated significantly over the past thirteen years, rising from 6.4% in 2000 to 10.3% by 2002, falling significantly to 4.1% by 2006, doubling to 8.4% during 2007 and stabilising between 5% and 7% in the years 2008 to 2012. Such sharp swings warrant an investigation to uncover the underlying drivers, and this paper finds evidence that the estimate of the saving rate correlates with a set of macroeconomic variables The results of an estimated equation are in line with the theory and robust to different estimation techniques.
Keywords: E32; E62; H20; H50; 330